(untitled) (Bangladesh Medical Journal, 2012)
Preeclampsia is a common pregnancy related disorder in Bangladesh that originates in the placenta and causes variable maternal and fetal problems. A prospective study was designed to see the associated maternal factors and fetal outcome in preeclampsia and to compare with that of normal pregnancy. The study was done in the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital and Mitford Hospital, Dhaka, from August 2005 to June 2006. Sixty Bangladeshi pregnant women were taken in this study, of which thirty were normal uncomplicated pregnancies (considered as control group or group A) and another thirty having pregnancies complicated by preeclampsia (considered as preeclampsia group or group B), where the patients were normotensive previously. Both the maternal and fetal outcomes were observed and recorded. The mean age of the mother was 26.53±5.26 years and 26.67±5.27 years in group A and group B respectively. The mean gestational age of the mother was 38.27±1.26 weeks and 36.90±1.03 weeks in group A and group B respectively and the difference in between two groups was statistically significant (p<0.001). The mean birth weight of the neonate was 2.80±0.27 kg. and 2.26±0.41 kg. in group A and group B respectively and the difference was significant (p<0.001). The mean APGAR score of the neonate at one minute was 9.00±1.02 and 8.40±0.93 in group A and group B respectively and the difference was significant (p<0.05). DOI: http://dx.doi.org/10.3329/bmj.v40i1.9960 BMJ 2011; 40(1): 33-36